2017
DOI: 10.3390/challe8020032
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Autonomous Vehicles on Consumers Time-Use Patterns

Abstract: Abstract:We use the American Time Use Survey (ATUS) to characterize how different consumers in the US might use Autonomous Vehicles (AVs). Our approach is to identify sub-groups of the population likely to benefit from AVs and compare their activity patterns with an otherwise similar group. The first subgroup is working individuals who drive to work with long total travel times. Auto-travelers in the top 20% of travel time number 19 million and travel 1.6 h more on a workday than those in the bottom 80%. For c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 30 publications
0
23
0
Order By: Relevance
“…Harper et al 2016 [37] found that if 69 million elderly, non-driving, and medically restricted people were to use AV to travel similar to current drivers, that would induce a 14% increase in light-duty vehicle miles traveled. Das et al 2018 [6] characterized what consumers would do inside an AV by analyzing the activities heavy drivers (2.5 hours of driving/day) sacrifice compared to the rest of the population (1 hour of driving/day): 30 minutes per day of sleep, watching video, and work, respectively. Scenario analysis is useful to identify issues and bound the magnitude of their effects; however, resulting bounds are wide, and when factors are summed, that can lead to uncertainty (e.g., in the net energy impacts of AVs) [36].…”
Section: Avs and Sustainability Research -Up To Nowmentioning
confidence: 99%
See 2 more Smart Citations
“…Harper et al 2016 [37] found that if 69 million elderly, non-driving, and medically restricted people were to use AV to travel similar to current drivers, that would induce a 14% increase in light-duty vehicle miles traveled. Das et al 2018 [6] characterized what consumers would do inside an AV by analyzing the activities heavy drivers (2.5 hours of driving/day) sacrifice compared to the rest of the population (1 hour of driving/day): 30 minutes per day of sleep, watching video, and work, respectively. Scenario analysis is useful to identify issues and bound the magnitude of their effects; however, resulting bounds are wide, and when factors are summed, that can lead to uncertainty (e.g., in the net energy impacts of AVs) [36].…”
Section: Avs and Sustainability Research -Up To Nowmentioning
confidence: 99%
“…For example, Harper and collaborators used this approach to scope how the elderly would use the technology by assuming older people with AVs would drive the same as younger people today with conventional vehicles [37]. Das et al compared workers with very long car commutes and shorter commute workers, postulating that the latent demand for activities lost to extra driving time is described by the activity patterns of the short commuting group [6]. In the third approach, mathematical models, generally based on utility optimization, are developed to simulate consumer choices [17].…”
Section: Avs and Sustainability Research -Up To Nowmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, AVs can have social impacts by providing independent mode of transportation for disabled and elder people. In addition, they can reduce the stress on the drivers and increase the utility of in-vehicle time by enabling the passengers to do other activities during travel time rather than driving tasks (Litman 2014, Das et al 2017.…”
Section: Benefits Of Autonomous Vehiclesmentioning
confidence: 99%
“…Scientists believe that the wide-scale implementation of AVs will bring transformative changes in mobility and accessibility, travel patterns, safety and security, energy efficiency, emissions, employment, data availability, governance and business models [4][5][6][7][8]. However, the scarcity of data for the real-life assessment of these changes often leads scientists to uncertain or even controversial conclusions.…”
Section: Introductionmentioning
confidence: 99%